2013
DOI: 10.9775/kvfd.2012.7161
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Total Serum Immunoglobulin E, A, G and M in Stray Dogs with Healthy and Dermatological Problems

Abstract: SummaryIn this study, clinical and laboratory findings along with serum IgE, IgA, IgM and IgG concentrations were determined in stray dogs (healthy and with dermatological problems). It was determined that skin lesions were localized in the rate of 69.8% (n=44) and generalized in the rate of 30.2% (n=19) of sick animals. Serum IgE concentration in stray dogs with dermatologic problems was significantly higher (P<0.001) than that of healthy dogs whereas serum IgM and G concentrations were significantly lower (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In dogs, abundant IgE production occurs as a result of the organism's type 1 hypersensitivity response to environmental allergens such as house dust mites, mould mites, wheat dust, grass or vernal grass allergens, pollen, epidermal antigens, insect antigens and feathers, resulting in a significant increase in serum IgE levels (Fraser et al., 2003 ). Many researchers (Maden et al., 2013 ; Pucheu‐Haston et al., 2015 ) have reported high IgE production in house dust mite‐induced atopic dermatitis in dogs. Allergen‐specific IgE concentrations were found to be higher in environmental mite‐induced atopy (Pucheu‐Haston et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In dogs, abundant IgE production occurs as a result of the organism's type 1 hypersensitivity response to environmental allergens such as house dust mites, mould mites, wheat dust, grass or vernal grass allergens, pollen, epidermal antigens, insect antigens and feathers, resulting in a significant increase in serum IgE levels (Fraser et al., 2003 ). Many researchers (Maden et al., 2013 ; Pucheu‐Haston et al., 2015 ) have reported high IgE production in house dust mite‐induced atopic dermatitis in dogs. Allergen‐specific IgE concentrations were found to be higher in environmental mite‐induced atopy (Pucheu‐Haston et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In atopic dermatitis, lesions occur on the face, concave surface of the auricle, lower abdomen, axilla, inguinal region, perineal region and distal extremities (Adam et al., 2022 ; Bizikova et al., 2015 ). Atopy is a type 1 hypersensitivity reaction of the body with immunoglobulin E (IgE) antibodies formed in the skin or in the blood circulation against environmental antigens (Maden et al, 2013 ; Olivry & Baumer, 2015 ; Pucheu‐Haston et al., 2015 ). Although environmental allergens such as indoor allergens, harmful dust, pollen, mould mites and grass play an important role in the aetiology of atopic dermatitis, it was reported that consumed allergenic foods also predispose to the disease (Bizikova et al., 2015 ; Pucheu‐Haston et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations